A Rare Case of Vascular Proliferation in the Mandible of a Juvenile Horse - Leitzen, Eva; Stumpf, Sebastian; Zimmermann, Claudia; Bienert-Zeit, Astrid; Hellige, Maren; Baumgärtner, Wolfgang; Puff, Christina (Frontiers in Veterinary Science, 2020)
A fast growing, circumscribed, unilateral swelling of the right mandible of a juvenile horse was observed. Within few weeks, the continuously growing mass reached dimensions ranging from 7 to 10 cm in diameter and resulted in loss of the first deciduous premolar of the affected side. The animal was euthanized due to lesion progression. Histologically the mandibular swelling consisted of numerous variably sized vascular structures, partly filled with erythrocytes and embedded in a loosely arranged fibrous stroma within the medullary cavity of the mandible. Juvenile mandibular angiomatosis was diagnosed. To the authors’ knowledge this is the first description of this rare entity in the mandible of a foal.